A comparative study of the response sets of the two groups of grade four pupils exposed to two types of curriculum materials in science - Belleza, Julita (Nadala) 1918- (s.n], 1971)
Based on the belief that curriculum materials and teaching methods greatly affect the reaction time, correctness of responses and clarity of explanations of the learners in solving problems, this investigation assessed the effectiveness of the SEC curriculum materials which has been used for 3 consecutive years at the University Elementary School.